Advanced Oxidation Processes Used in The Treatment of Perfluoroalkylated Substances in Water - María Lizeth Marín-Marín (Revista UIS Ingenierías, 2023)
Perfluoroalkylated and polyfluoroalkylated substances (PFAS) are a large family of synthetic chemicals widely used to manufacture various commercial products. However, they are hazardous to health and the environment. These substances are very persistent and their degradation requires advanced degradation techniques. One of the most widely used technologies for this purpose is advanced oxidation processes (AOP). This study aims to evaluate the use of AOP in PFAS degradation based on their efficiency, parameters influencing each process, advantages, disadvantages, and associated research challenges. According to the results, plasma, electrochemical oxidation, sonochemical oxidation, and heterogeneous photocatalysis stand out among the AOP applied for PFAS degradation. In addition, perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) were found to be the main toxic compounds studied. In this regard, future research should focus on a wider variety of PFAS. Finally, the drawbacks associated with the application of these processes to eliminate the substances of interest were found to be an urgent need to be overcome.